(untitled) (Journal of Atomic and Molecular Sciences, 2012)
Electron scattering by lead atom is studied at energies 10, 20, 40, 60, 80 and 100 eV by applying a parameter-free complex optical potential. The real part of the complex optical potential includes the static potential V_st(r), the polarization potential V_pol(r) that consists of the short-range correlation and long-range polarization effects and V_ex(r, k) term consisting of electron exchange interaction which is modeled by assuming the electron charge cloud as a free electron gas. The loss of flux into the inelastic channels is included via a phenomenological absorption potential. Our results are compared with the recent theoretical and experimental measurements.